Grading Standards in Education Departments at Universities - Koedel, Cory (Education Policy Analysis Archives, 2011)
Students who take classes in education departments at universities receive significantly higher grades than students who take classes in other academic departments. The higher grades awarded by education departments cannot be explained by differences in student quality or by structural differences across departments (i.e., differences in class sizes). The remaining explanation is that the higher grades are the result of lower grading standards. This paper formally documents the grading-standards problem in education departments using administrative grade data from the 2007-2008 academic year. Because a large fraction of the teachers in K-12 schools receive training in education departments, I briefly discuss several possible consequences of the low grading standards for teacher quality in K-12 schools.